Study of Solid State Reaction Involved in Synthesis of Nano Structured Th0.9Ce0.1O2 - Arora Chugh, C.; Banthiya, A.; Deepika; Bharti, D.; Ramarao, G.A.; Naik, Y.P. (Asian Journal of Chemistry, 2012)
In the present paper, fuel for advanced heavy water reactor (AHWR) is simulated using thorium oxide with varying quantities of cerium oxide. Two mixed oxides were synthesized. GEL combustion technique was applied to attain oxides of thorium and cerium from their respective nitrate using citric acid as the gelating agent. The dried samples were characterized by IR and TGA studies. Intermediate and final products during TGA studies have been isolated and characterized by XRD studies. All the TGA runs during heating of thorium and cerium nitrate with citric acid dried Gels showed a two step process. The weight loss studies and the X-ray data of the product, helped in suggesting a possible mechanism. Kinetic study was carried out independently for each step. The reaction mechanism as observed during interactive procedure was diffusion controlled. The kinetic parameters (activation energy and pre-exponential factor) for each step in all reactions have been calculated. XRD studies show that with increase in cerium concentration in the oxides, the lattice parameter values have shown a decreasing trend for all the compositions studied. It was observed that in TGA studies with increase in cerium concentration, the final temperature of the reactions have shown a decreasing trend. Model fitting for the reaction suggested that the reaction obeyed Avrami-Erofeev solid diffusion controlled model represented by the kinetic equation: k*t = [-ln (1-a)]3/4 The rate constant for this first step reaction was determined as function of temperature. A least square line could be fitted to the value of k obtained at different temperatures. It is observed that rate constant is related to temperature as per the equation: ln k = 51.23-82620.5/T (for first step) ln k = 50.02-40079.2/T (for second step) SEM studies of the powders reveal that the synthesized oxides have a tendency to form agglomerate of varying size ranging from 50-100 μm in case of mixed oxides but the size of thorium oxide powder so synthesized have pore size 10-100 μm. SEM studies also reveal that each agglomerate contains approximately 10-100 individual particles.